Decreased Anxiety of Pregnant Women with Endorphine Massage on the Preoperation of Sectio Caesarea - Raden Nety Rustikayanti; Yulia Anugrah; Inggrid Dirgahayu; Tri Nur Jayanti; Cucu Rokayah (GLOBAL HEALTH SCIENCE GROUP, 2022)
Maternal anxiety facing sectio caesarea that is not treated properly can cause physical and psychological changes that can eventually increase the work of sympathetic nerves and there will be an increase in heart rate, breath frequency, blood pressure, and in general reduce energy levels in patients to the detriment of patients. The purpose of this study was to determine the effectiveness of endorphine massage against sectio caesarea preoperative anxiety in primigravida mothers in the Central Surgery Room of Bandung City Hospital. The research design is a Quasi-Experiment using experimental groups and control groups. The population is 193 people. The samples used for each group were 18 people with a purposive sampling technique. Data collection was carried out using the Hospital Anxiety Depression Scale questionnaire. Data analysis used bivariate analysis in the form of the Wilcoxon test and the Mann Whitney test. The results of the study found that anxiety before the endorphine massage intervention was mostly moderate 14 people (77.8%) and after the intervention more than half were mild 12 people (66.7%). Before the deep breath relaxation intervention was mostly moderate 16 people (88.9%) and after the intervention more than half were moderate 13 people (72.2%). There is an effect of endorphine massage on anxiety (p-value 0.000 < 0.05). There is an effect of deep breath relaxation on anxiety (p-value 0.004 < 0.05). There is a difference in anxiety between the intervention of endorphine massage with deep breath relaxation and endorphine massage is more effective than deep breath relaxation (p-value 0.003 < 0.05). Endoprhine massage intervention can overcome anxiety problems because it can stimulate endorphine hormones which can provide a comfort effect. The conclusion was found that endorphine massage can reduce anxiety. Advice for hospitals can make endoprhine massage a standard operating procedure in dealing with anxiety problems of preoperative patients.